2008
DOI: 10.1021/jp8053636
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Monodisperse Magnetic Nanoparticles Protected by an Amphiphilic Alternating Copolymer

Abstract: Iron oxide nanoparticles (NPs) with diameters of 16.1, 20.5, and 20.8 nm prepared from iron oleate precursors were coated with poly(maleic acid-alt-1-octadecene) (PMAcOD). The coating procedure exploited hydrophobic interactions of octadecene and oleic acid tails while hydrolysis of maleic anhydride moieties allowed the NP hydrophilicity. The PMAcOD nanostructure in water and the PMAcOD-coated NPs were studied using transmission electron microscopy, ζ-potential measurements, small-angle X-ray scattering, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 65 publications
2
73
3
1
Order By: Relevance
“…We found that a small nanoparticle with a poly(maleic anhydride-alt-1-octadecene)-coat [25,30] seemed to accumulate selectively in liver sinusoidal endothelium ( Supplementary Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a small nanoparticle with a poly(maleic anhydride-alt-1-octadecene)-coat [25,30] seemed to accumulate selectively in liver sinusoidal endothelium ( Supplementary Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…59 Fe-labelled [22] and unlabelled [23] superparamagnetic iron-oxide nanocrystals or CdSe/CdS/ZnS-core-shellshell quantum dots [24] were encapsulated into an amphiphilic polymer (poly(maleic anhydride-alt-1-octadecene)as described [25]. Coupling of nanoparticles (6 µmol/l) to peptides with 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (6 mmol/l) was conducted as described [26].…”
Section: Experimental Autoimmune Encephalomyelitis 200 µG Mbp Peptidmentioning
confidence: 99%
“…Poly(maleic anhydride-alt-1-octadecene) (PA-18) is an amphiphilic copolymer [32]. Coating of a hydrophobic surface with this copolymer in an aqueous environment could lead to an ordered arrangement of the amphiphilic molecules, resulting in the exposure of their hydrophilic portions, thus rendering the surface more hydrophilic.…”
Section: Effects Of Surface Treatments On the Hydrophilicity Of Pes/pmentioning
confidence: 99%
“…40 This method has yielded exceptionally stable and biocompatible NPs, but the high cost of PEGylated phospholipids limits their potential applications and has stimulated research for more affordable amphiphilic molecules. 41 …”
Section: Spion Size and Coatingsmentioning
confidence: 99%